2005
DOI: 10.1192/bjp.187.6.552
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in individuals who have had psychiatric treatment

Abstract: Mortality risk is increased in all psychiatric patients, not just those who have received in-patient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 25 publications
7
79
0
1
Order By: Relevance
“…A number of studies have previously found an association between PD and raised mortality [12][13][14][15][16]. However, to our knowledge, our study is the first to comprehensively examine the life expectancy of secondary care service users with PD.…”
Section: Main Findingsmentioning
confidence: 91%
See 1 more Smart Citation
“…A number of studies have previously found an association between PD and raised mortality [12][13][14][15][16]. However, to our knowledge, our study is the first to comprehensively examine the life expectancy of secondary care service users with PD.…”
Section: Main Findingsmentioning
confidence: 91%
“…It is one of the hardest psychiatric conditions to treat and has a considerable economic impact on general medical and mental health services. People with personality disorder (PD) are known to be at particularly high risk of increased mortality as a result of both natural and unnatural causes [12][13][14][15][16]. However, no study has comprehensively examined life expectancy at birth of the full range of secondary care service users with PD.…”
Section: Introductionmentioning
confidence: 99%
“…El tratamiento antipsicótico siempre se ha asociado a estas alteraciones cardiometabólicas, sin embargo, la evidencia muestra que pacientes que nunca han recibido tratamiento también presentan estas patologías concomitantes 4 , además que muchas de ellas se encuentran desde el primer episodio psicótico, por ende, se postula que la EQZ per se estaría relacionada con esta alteración 5,6 .…”
Section: The Life Expectancy Of Patients With Schizophrenia (Sch) Is unclassified
“…[1][2][3][4][5] Higher mortality is frequently associated with 'lifestyle choices', such as smoking, poor diet, physical inactivity, substance misuse and abuse and unsafe sexual practices. 3,6 However, even after adjusting for behavioural risk factors, mortality remains high for this population.…”
Section: Introductionmentioning
confidence: 99%